USABILITY ANALYSIS OF THE LASIRAH “LANCAR ASI SEHAT IBU RIANG ANAK DAN HAPPY“ APPLICATION WITH THE USE QUESTIONNAIRE - Siti Rochana; Septi Tri Aksari (Universitas Kadiri, 2026)
Introduction: The postpartum period is a crucial phase for mothers in maintaining exclusive breastfeeding. Low self-efficacy and postpartum depression are major barriers to breastfeeding success. Advances in digital technology offer opportunities to enhance maternal independence through innovations. Aims: This study aimed to analyze the usability level of the LASIRAH (Lancar ASI Sehat Ibu Riang Anak dan Happy). Method: The study used a quantitative descriptive design with a cross-sectional method. The subjects were 30 postpartum mothers who used the LASIRAH application for 7 days, selected using a purposive sampling technique. Usability was measured using the USE Questionnaire, which covers the dimensions of usefulness, ease of use, ease of learning, and satisfaction. Data were collected using a 1–4 Likert scale questionnaire and analyzed descriptively as part of a formative usability evaluation. Result: The overall usability score was 84.54%, categorized as very feasible. Specifically, the usefulness dimension scored 86%, ease of use 84.5%, ease of learning 83.5%, and satisfaction 84.15%. These results indicate that LASIRAH is highly useful, easy to use and learn, and provides high user satisfaction. Conclusions and Suggestions: LASIRAH shows strong potential for broader implementation to enhance breastfeeding self-efficacy and prevent postpartum depression through a user-centered digital health approach.